Interventions to improve antiretroviral adherence in HIV-infected pregnant women: A systematic review and meta-analysis - Zhou, Jie; Yun, Jingyi; Ye, Xinxin; Liu, Wen; Xiao, Wenhan; Song, Peige; Wang, Hongmei (Frontiers in Public Health, 2022)
Background: Medication adherence in HIV-infected pregnant women remains suboptimal. This systematic review and meta-analysis aimed to evaluate the effectiveness of interventions on improving antiretroviral adherence targeting among HIV-infected pregnant women. Methods: Five databases were screened to identify quasi-experimental studies and randomized controlled trials. The risk ratios (RR) and confidential intervals (CI) were extracted to estimate the improvement in antiretroviral adherence after interventions compared with control conditions. This study was registered with PROSPERO, number CRD42021256317. Results: Nine studies were included in the review, totalling 2900 participants. Three interventions had significance: enhanced standard of care (eSOC, RR 1.14, 95%CI 1.07-1.22, Z=3.79, P<0.01), eSOC with supporter (RR 1.12, 95%CI 1.04-1.20, Z=2.97, P<0.01) and device reminder (RR 1.33, 95%CI 1.04-1.72, Z=2.23, P=0.03). Discussion: The study supported the eSOC and the device reminder as effective intervention strategies for improving HIV medication adherence. Based on the current findings, the study called for more efforts to improve antiretroviral care for pregnant women through involving multicentre, large-sample, and high-quality research and combining the device reminder with other intervention methods.